Fiber‐Integrated Phase Change Metasurfaces with Switchable Group Delay Dispersion. Issue 21 (17th August 2021) - Martins, Tiago; Cui, Yihao; Gholipour, Behrad; Ou, Jun‐Yu; Frazão, Orlando; MacDonald, Kevin F.
Abstract: Demonstration of a fiber‐integrated non‐volatile reconfigurable metasurface providing high‐contrast group delay dispersion switching functionality is reported, which may be engineered to operate at wavelengths across the near‐infrared (telecoms) band. Light‐induced amorphous‐crystalline phase switching in a chalcogenide (germanium antimony telluride) metasurface, only a fraction of a wavelength thick, fabricated on the end‐facet of a single‐mode optical fiber, enables intensity and phase modulation of the guided wave at metasurface designated bands. Such devices present a range of opportunities in fiberized remotely programmable phase/intensity multiplexing and dynamic dispersion compensation for emerging telecommunications and data storage/processing applications, including in photonic neural network and neuromorphic computing architectures. Abstract : Light‐induced amorphous‐crystalline phase switching in a chalcogenide metasurface, fabricated on the end‐facet of a single‐mode optical fiber, enables intensity and phase modulation of the guided wave at metasurface designated bands. Such devices present a range of opportunities in fiberized remotely programmable phase/intensity multiplexing and dynamic dispersion compensation for emerging telecommunications and data storage/processing applications.